Energy flow and ground reaction force predictors of bat swing speed during pitched ball batting in professional baseball players - Hashimoto, J.; La Salle, D. T.; Takata, A.; Aguinaldo, A.; Wasserberger, K. (ISBS Proceedings Archive (Michigan), 2023)
The purposes of this study are to determine how mechanical energy is absorbed, generated, and transferred during baseball hitting for professional athletes. This study also aims to identify which ground reaction force and energy flow variables influence bat speed. The findings of this study suggest that energy flows from the trunk to the lead leg as the pelvis rotates towards the pitcher. The results of this study emphasize the crucial role of the back leg and trunk during acceleration as well as eccentric contraction of muscles in the lead leg and trunk to decelerate during follow-through. Training strategies that improve muscular strength and mobility of the trunk and hips can be implemented to potentially increase bat speed.